2009
DOI: 10.1089/jmf.2008.0120
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Antibacterial, Antiproliferative, and Antioxidant Potentials and DNA Damage-Protecting Activity ofAcacia salicinaExtracts

Abstract: The extract enriched in total oligomer flavonoids (TOF), and the aqueous, methanol, and ethyl acetate extracts of Acacia salicina were investigated for their polyphenolic compound content, antioxidative activity in the nitro blue tetrazolium/riboflavin assay system, antibacterial activity against Gram-positive and Gram-negative bacterial reference strains, antigenotoxic activity tested with the Ames assay, and cytotoxic activity against the K562 human chronic myelogenous leukemia cell line and L1210 leukemia m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Little information is available on antioxidants from Acacia seeds. For Acacia salicina the phenolic content of leaves was ca 0.18 g GAE kg −1 DW 24. The values obtained for A. cyanophylla were lower than those reported by Elfalleh et al 22 for pomegranate seeds (11.84 g RE kg −1 DW) and by Velioglu et al 25 for sunflower seeds (16.01 g kg −1 DW), buckwheat seeds (7.26 g kg −1 DW) and wheat germ (3.49 g kg −1 DW).…”
Section: Resultsmentioning
confidence: 99%
“…Little information is available on antioxidants from Acacia seeds. For Acacia salicina the phenolic content of leaves was ca 0.18 g GAE kg −1 DW 24. The values obtained for A. cyanophylla were lower than those reported by Elfalleh et al 22 for pomegranate seeds (11.84 g RE kg −1 DW) and by Velioglu et al 25 for sunflower seeds (16.01 g kg −1 DW), buckwheat seeds (7.26 g kg −1 DW) and wheat germ (3.49 g kg −1 DW).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation with antioxidants offers protection against oxidative stress and free radical damage. 32,33 PAE and PAM exhibited promising total antioxidant potential. PAE showed significant ABTS radical decolorisation potential (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that depletion of antioxidant status in patients with type 2 diabetes mellitus is responsible for the early onset of secondary complications. Supplementation with antioxidants offers protection against oxidative stress and free radical damage . PAE and PAM exhibited promising total antioxidant potential.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, antibacterial activity of aqueous, methanolic and ethyl acetate extracts of Acacia salicina Lindl. against Staphylococcus aureus and Salmonella serovars Enteritidis and Typhimurium has been reported 13. Also, aqueous and methanolic extracts of Schizandrae Fructus ( Schisandra chinensis (Turcz.)…”
Section: Introductionmentioning
confidence: 99%